Strouhal number effects on dynamic boundary layer evolution over a wedge surface from initial flow to steady flow: analytical approach - Bachiri, Mohamed; Bouabdallah, Ahcen (Zielona Góra: Uniwersytet Zielonogórski)
The present work studies the effects of the physical parameter characterizing the laminar flow regime, namely the Strouhal number, on the evolution of the unsteady dynamic boundary-layer developed along a wedge surface. Similarity method is used to transform unsteady momentum equation to dimensionless form.
Keywords: unsteady boundary layer; wedge surface; Strouhal number; superposition method; diffusion; convective